Journalistic quality in the treatment of gender-based violence against women: Caracol Noticias case/Calidad periodística en el tratamiento de la violencia de género contra las mujeres: el caso de Caracol Noticias (Encuentros, 2018)
The purpose of this article was to know the characterization of the journalistic treatment of news about violence against women due to gender. For an approximation to the object, News Caracol, of Canal Caracol Television in Colombia, was analyzed. To this end, the news content broadcast by the channel about cases of gender violence during the years of 2013 and 2014 was made available through the You Tube channel of the news program in question. As part of the findings, there was a scarce presence of the topic in the news agenda and the low importance that has been given to the problem, as well as a ritualization in the presentation of the events, the protagonists and the causes, did not contribute that the audiences see critically the motivations of the aggressor and neither generates critical conscience due to the lack of expert sources on this systematic violation of Human Rights.Key words: gender violence, patriarchy, information treatment and content analysis.